PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN PENGUNJUNG MUSEUM KARTINI JEPARA (Management Analysis Journal, 2013)
This study aimed to determine: (1) the effect of service quality on customer satisfaction. (2) the value of customers to customer satisfaction. The population in this study are all Jepara Kartini museum visitors. The sampling technique used was nonprobability sampling with accidental sampling approach number 96. The results showed the results of the regression equation Y = 9,468 + 0,282X1 + 0,407X2, namely (1) service quality has positive and significant impact on customer satisfaction with a significant value of 0.000 <0.05, so the first hypothesis is accepted. (2) the negative impact of customer value and significant impact on customer satisfaction with a significant value of 0.003 <0.05, therefore the second hypothesis is accepted.